Agribusiness Indicators : Tanzania - World Bank (World Bank, Washington, DC, 2017)
Agriculture in Tanzania accounts for 28 percent of the country's Gross Domestic Product (GDP) and employs 80 percent of its labor force. The sector is also an important source of export revenues. The data and findings presented in this report provide a summary of the performance of the agriculture sector in Tanzania using a set of indicators covering six areas. These are: 1) access to and availability of certified seed; 2) availability of and access to fertilizer; 3) access to farm machinery, particularly tractor hire services for land preparation; 4) access to agricultural and agro-enterprise finance; 5) the cost and efficiency of transporting agricultural commodities; and 6) measures of policy certainty and uncertainty as perceived by private investors and the effects these have on the enabling environment for producers and agribusinesses. The Agribusiness Indicators (ABI) team conducted interviews with Government agencies, private firms (fertilizer importers, seed companies, tractor importers and distributors, transporters), commercial banks, farmer-based organizations, donors, and Non Governmental Organizations (NGOs). The ABI program is pilot testing an initial set of indicators on the ease (or difficulty) of operating agribusinesses in African countries. The indicators are used to assess whether the countries have an enabling environment that is conducive to agribusiness investment, competitiveness, and ultimately agriculture-led growth.